Preventing Child Sexual Abuse Early: Preschool Teachers' Knowledge, Attitudes, and Their Training Education in China. (4th February 2015) - Zhang, Wenjing; Chen, Jingqi; Liu, Fengfeng
This study is aimed to examine preschool teachers' knowledge of, attitudes about, and training related to child sexual abuse (CSA) prevention in Beijing, China. Two hundred and forty-five preschool teachers were administered the 16-item questionnaire that contained questions on CSA prevention knowledge, attitudes, and teacher training. Results showed that Chinese preschool teachers had limited knowledge on CSA prevention ( M = 4.86, SD = 2.12). Less than 5% of the teachers ever attended CSA prevention training programs. Preschool teachers' training on CSA prevention was the significant factor for their knowledge and attitudes. To help protect children against sexual abuse, there is an urgent need to develop appropriate prevention training programs for preschool teachers in China.